Responding Strategies to Greetings and Invocations in Jordanian Arabic in CCCS Interactions: A Socio-Pragmatic Study - Amer, Faten; Buragohain, Dipima; Suryani, Ina (European Scientific Journal, ESJ, 2020)
This paper focuses on examining the types of responding strategies employed in the interactions between Jordanians and the employees of the call-centre-customer service (CCCS) of a major telecommunications company in Jordan. It focuses on their linguistic behaviours upon responding to greetings and invocations. Naturally-occurring interactions and designed situations were used to collect data from 28 Jordanian Arabic speakers who participated in this study. Data were transcribed and translated into English and further divided into groups according to types of participants’ responses to greetings and invocations. The results revealed that responses to greetings were different based on their length and type, whereas responses to invocations usually involved a response that included the same invocation. Furthermore, it has been revealed that participants are impacted by the socioreligious norms of the Jordanian society.